STRESS MANAGEMENT AND POSITIVE ORGANISATIONAL SCHOLARSHIP - Jain, Shriyak; Singh, Amar Inder (Central Asian Journal of Theoretical and Applied Science, 2022)
Stress management in today’s world is the most crucial subject to study to understand the Stressors at workplace. It is important to understand the factors contributing to stress and ways of handling it. The process of Positive organisational scholarship is dedicated to construct a better place through logical scientific way and management practices of thriving organisations. Positive organisational scholarship reveals and nurtures the highest level of human potential and helps employees in questioning themselves about what makes them thriving, how can they cruise their organisation in difficult times as stronger as before. Infusing POS at workplace may decrease the level of stress in organisation as positivity would diminish the negativity which would decrease the stress. The research paper will study the consequences and sources of stress and How Positive organisational scholarship Practices would try to reduce stress in the organization. The pillars of POS which is thriving, abundance, excellence, resilience and virtuousness will impact the job performance. The research paper is conceptual in nature. It is designed using theories and grounds from various Researches. Moustaka, E., & Constantinidis, T. C. (2010). Sources and effects of work-related stress in nursing. Health science journal, 4(4), 210. Avoiding tragedy and failure or coping admirably with setbacks or misfortune are a part of Domain of POS. POS will fill the hope and optimism in the employees which will influence the job performance.